Los costos de la panela en la Unidad Productiva del Señor José Edwin Briceño Castillo de la Parroquia Quinara, Cantón Loja, periodo octubre-diciembre 2022 - Briceño Jiménez, Katia María (2024)
In the Curricular Integration Work entitled "LOS COSTOS DE LA PANELA EN LA UNIDAD PRODUCTIVA DEL SEÑOR JOSÉ EDWIN BRICEÑO CASTILLO DE LA PARROQUIA QUINARA, CANTÓN LOJA, PERIODO OCTUBRE - DICIEMBRE 2022," a costing system was implemented to determine the total and unit costs that impact the production process. The first objective, which involved creating a plan and account manual where each account is coded and described, was fulfilled. Auxiliary records were designed to control the three elements of cost, namely: production order, receipt report, requisition order, Kárdex, time card, worksheets, payroll, provisions schedule, and cost sheet. The accounting process began with the initial inventory, which involved a physical verification of the assets, values, and liabilities of the business. Using this information, the Initial Financial Position Statement was prepared, transactions were recorded in the General Journal, and the values were transferred to the General Ledger. The resulting balances were used to determine the Trial Balance, which served as the basis for preparing the worksheet with corresponding adjustments. This process allowed for the determination of the Cost of Goods Sold Statement with a total value of $35,117.04. The Income Statement reflects a profit before taxes of $6,516.86, and the Financial Position Statement shows total assets of $60,833.21, liabilities of $36,833.88, and equity of $23,999.33. The methodology applied the scientific method to explain and justify the procedures carried out in the company. Additionally, deductive, inductive, analytical, and mathematical methods and research techniques such as observation and bibliographic compilation were used. Through the execution of the accounting process, the total and unit cost of panela was determined, providing results that will facilitate decision-making to enhance business development.